PENGARUH SUKU BUNGA, EKSPOR, DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT INFLASI DI INDONESIA - Muntaza, Farah Isnani; Susilowati, Dwi (Journal of Financial Economics & Investment, 2024)
Inflation has always been a major concern of governments in the world, especially in developing countries like Indonesia, as an economic issue. The study aims to study how economic growth, exports, and interest rates impacted inflation rates during the period 1993-2022. Interest rates, exports, and economic growth are used as free variables, and inflation is used as bound variables. In this study, the analysis method is a double linear regression analysis. The results show that export value has a significant positive influence on inflation, while interest rates and economic growth have a significant negative influence upon inflation. Reducing aggregate economic demand, which can suppress inflationary pressures, is a way to control interest rates. To suppress inflation during economic growth, tax policies can be used to reduce public spending or raise taxes.